G4-Interacting DNA Helicases and Polymerases: Potential Therapeutic Targets - Estep, Katrina N. (Curr Med Chem, 2019)
Guanine-rich DNA can fold into highly stable non-canonical four-stranded DNA structures called G-quadruplexes. These structures present obstacles for the DNA replication machinery, and it has been hypothesized that both eukaryotic DNA helicases and polymerases have evolved to resolve G4 DNA in vivo. Since the discovery of G-quadruplex DNA in the early 1960’s, a number of studies have emerged reporting G-quadruplex DNA unfolding by helicase enzymes and DNA synthesis past G4 by specialized translesion polymerase enzymes. Recently, the discovery of the primase-polymerase PrimPol and its role in G4 bypass has sparked even more excitement in the G-quadruplex and DNA replication fields. This review presents an overview of the molecular interactions of G-quadruplexes with DNA helicases and polymerases implicated in their resolution, with an emphasis on how the regulation and coordination of these enzymes is critical for genome homeostasis. Targeting G4-interacting DNA helicases and polymerases for therapeutic strategies is discussed.